2019
DOI: 10.1016/j.ccell.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacogenomic Landscape in Human Liver Cancers

Abstract: Highlights d Liver Cancer Model Repository (LIMORE) consists of 81 liver cancer cell models d LIMORE recapitulated genetic heterogeneity of human liver cancers d Molecular and drug screenings provide a pharmacogenomic landscape in liver cancers d Interrogation of the landscape informs biomarkers for liver cancer treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 85 publications
(118 reference statements)
6
133
0
Order By: Relevance
“…(40) It was therefore surprising that mTOR inhibition did not significantly alter HCC viability in the setting of purine synthesis inhibition, consistent with a previous report showing a mode of PI3K regulation of purine synthesis independent of mTOR/S6 kinase in mouse embryonic fibroblasts and C2C12 myoblasts. (41) In the context of HCC, a recent study comparing the responses of 81 HCC cell lines to a panel of anticancer drugs demonstrated that, despite rapamycin and PI-103 eliciting similar sensitivities in many lines, a significant fraction exhibited opposing vulnerabilities to PI3K or mTOR inhibition, (31) attesting to a subset of HCC wherein mTOR is dispensable for PI3K regulation. Here, we demonstrate that PI3K signaling modulates E2F1 occupancy on purine synthetic gene promoters through RB phosphorylation, thus relieving sequestration of E2F1 to RB, consistent with a role for E2F1 in regulating the cell cycle and metabolic adaptations of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(40) It was therefore surprising that mTOR inhibition did not significantly alter HCC viability in the setting of purine synthesis inhibition, consistent with a previous report showing a mode of PI3K regulation of purine synthesis independent of mTOR/S6 kinase in mouse embryonic fibroblasts and C2C12 myoblasts. (41) In the context of HCC, a recent study comparing the responses of 81 HCC cell lines to a panel of anticancer drugs demonstrated that, despite rapamycin and PI-103 eliciting similar sensitivities in many lines, a significant fraction exhibited opposing vulnerabilities to PI3K or mTOR inhibition, (31) attesting to a subset of HCC wherein mTOR is dispensable for PI3K regulation. Here, we demonstrate that PI3K signaling modulates E2F1 occupancy on purine synthetic gene promoters through RB phosphorylation, thus relieving sequestration of E2F1 to RB, consistent with a role for E2F1 in regulating the cell cycle and metabolic adaptations of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…HCCs exhibit extensive heterogeneity with regards to proteomic, metabolomics, and immune profiles as well as responses to anticancer drugs, contributing to different metabolic requirements across tumors. (31,32) We hypothesized that every tumor would thus have a unique growth dependency on IMPDH-driven purine biosynthesis and demonstrate varying sensitivities and tolerance toward MPA. PDX mouse models offer a clinically relevant system to test this hypothesis, with drug studies being able to be performed in vivo as well as in vitro on PDX organoids in the context of heterogeneous molecular alterations in patients.…”
Section: Heterogeneity In Purine Synthetic Pathway Activity Determinementioning
confidence: 99%
“…Biological and clinical heterogeneity among otherwise histologically indistinguishable tumors explains the vast majority of therapeutic failures and provides the major rationale for individualizing, or "personalizing", cancer treatment. Thus far, the means of attaining such precision medicine-based goals has involved a combination of improved clinical staging; high-resolution imaging techniques; immuno-histochemical-based tumor sub-classification and, increasingly, molecular and pharmacogenomic evaluation to stratify individuals according to inherent risk and likelihood of response to chemotherapeutic regimens [5,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. The deployment of newer techniques such as liquid biopsies, which quantify circulating tumor DNA, promise to provide additional benefits by allowing serial assessments of response to therapy or the detection of impending recurrence in cases where the tumor has been previously resected or otherwise rendered undetectable by standard methods [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the majority of patients were diagnosed at an advanced clinical stage, especially in Eastern Asia and sub-Saharan Africa, cancer-speci c mortality still continues to climb [3]. Substantial advances have been made to understand the detail mechanism of tumor transformation and HCC progression [4,5]. Accumulating ndings of factors contributing to the development of targeted drugs, systemic therapy for HCC patients has made great progress [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial advances have been made to understand the detail mechanism of tumor transformation and HCC progression [4,5]. Accumulating ndings of factors contributing to the development of targeted drugs, systemic therapy for HCC patients has made great progress [4,5].…”
Section: Introductionmentioning
confidence: 99%